Bacterial vaginosis: comparative effectiveness of treatments with 5-nitroimidazole derivatives - I.G. Kutsenko; I.O. Borovikov; E.I. Kravtsova; S.K. Batmen; A.S. Magay; O.I. Borovikova; V.A. Avakimyan; A.A. Andreeva (LCC «Medicine-Inform», 2023)
I.G. Kutsenko, I.O. Borovikov, E.I. Kravtsova, S.K. Batmen, A.S. Magay, O.I. Borovikova, V.A. Avakimyan, A.A. Andreeva Kuban State Medical University, Krasnodar, Russian Federation Aim: to perform a comparative analysis of clinical and microbiological efficacy and compliance to treatment with 5-nitroimidazole derivatives in patients with bacterial vaginosis (BV). Patients and Methods: this prospective open randomized study included 96 patients diagnosed with BV. The patients were divided into two groups: group 1 (n=48) received antimicrobials - oral secnidazole 2000 mg in a single dose (decontamination therapy) and vaginally administered L. casei rhamnosus Doderleini for 14 days to restore the vaginal flora (contamination therapy); group 2 (n=48) received oral metronidazole 500 mg twice daily for 7 days (decontamination therapy) and vaginally administered L. casei rhamnosus Doderleini for 14 days (contamination therapy). Clinical efficacy was evaluated one and six months after the end of therapy. The treatment efficacy criteria included the absence of specific patient's complaints, clinical and laboratory findings (pH; Nugent score), and PCR results. The compliance to treatment was assessed using clinical and psychological tests (the Morisky-Green Scale and the Modified Medication Compliance Scale). The assessment of safety profile was based on the analysis of adverse events (AE). Results: one month after the end of treatment all patients had a statistically significant (p<0.05) reduction in the prevalence of BV symptoms (unpleasant vaginal odor, pathological vaginal discharge, itching, dyspareunia, dysuria events) as compared to those at the baseline. At month 1 after the end of treatment, subgroup analysis did not demonstrate a significant difference. Six months after the end of treatment the proportion of the group 1 patients who had pathological vaginal discharge with specific odor increased to 16.7%, while in the group 2 patients it reduced to 8.3% (p<0.05). Microbiological assessment (PCR) of the combination therapy in two groups of patients with BV demonstrated a high antibacterial efficacy of 5-nitroimidazole derivatives during the first month of follow-up. The patients were considered fully compliant if they scored 4 on the Morisky - Green Scale and scored 30 on the Modified Medication Compliance Scale of V.M. Bekhterev National Medical Research Center for Psychiatry and Neurology. The percentage of full compliance was 76.2±2.8% in the group 1 patients and 93.75±3.25% in the group 2 patients. Conclusion: a high comparative clinical and microbiological effectiveness of treatments with 5-nitroimidazole derivatives (metronidazole and secnidazole) with further vaginal colonization with lactobacilli was demonstrated in patients with bacterial vaginosis. Full medication compliance was higher in patients receiving secnidazole for BV treatment. Keywords: bacterial vaginosis, vaginal microbiota, vaginal discharge, 5-nitroimidazole derivatives, metronidazole, secnidazole, compliance. For citation: Kutsenko I.G., Borovikov I.O., Kravtsova E.I. et al. Bacterial vaginosis: comparative effectiveness of treatments with 5-nitroimidazole derivatives. Russian Journal of Woman and Child Health. 2023;6(2):78-87 (in Russ.). DOI: 10.32364/2618-8430-2023-6-2-78-87.